Dopamine reveals neural circuit mechanisms of fly memory - Waddell, Scott (2010)
A goal of memory research is to understand how changing the weight of specific synapses in neural circuits in the brain leads to an appropriate learned behavioral response. Finding the relevant synapses should allow investigators to probe the underlying physiological and molecular operations that encode memories and permit their retrieval. In this review, I discuss recent work in Drosophila that implicates subsets of dopaminergic neurons in aversive reinforcement and appetitive motivation. The zonal architecture of these dopaminergic neurons may reveal the functional organization of aversive and appetitive memory in the mushroom bodies. Combinations of fly dopaminergic neurons might code negative and positive value consistent with a motivational systems role proposed in mammals.